Teaching Creative Digital Hardware Design - Mohd Zainee, Norhayati; Noras, James M. (Elsevier, 2013)
Engineering undergraduates not only need to learn facts, but also how to be creative in the open-ended situations they will encounter in their professional careers. Our final year Honours module gives students a grounding in digital systems design, mainly using VLSI for design entry and simulation. The second half of our module is a design exercise, which has straightforward aspects, but which allows motivated students to undertake progressively open-ended investigations. Our educational framework is guided by recommendations of professional bodies promoting excellence and encouragement of creativity in engineering development.